Method and Models in Administrative Canon Law - GHERRI, PAOLO (Prawo Kanoniczne, 2013)
The administrative canon law still lacks a true canonical method to become a science in a true sense. Until now, the canonists have used administrative models derived from the Civil Law Countries (Italy and France, first of all). Such models, however, do not explain enough, and often make the administrative canonical system incomprehensible by imposing stretching and distortions. An illustration of some large and irreducible differences between the administrative State systems and the canonical one is now needed to incite to abandon the State model and look into the “global” Administrative Law for explanations and better prospects.